EXPLORING THE LOW RATE OF BPR CUSTOMER GROWTH IN JAKARTA - Sadat, Andi Muhammad (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2017)
Since mid of 2015, the number of BPR customer has declined (Joko Suyanto in Linangkung, 2016). This study intends to describe what factors that influence the low rate of BPR customer growth in Jakarta. The explorative approach was done by employing samples in two steps. First, interviews were conducted on 10 market participants followed by FGD (focus group discussion) to 32 respondents in one of the largest â€œpasar indukâ€ in Jakarta. Second, FGD results become the guideline for arranging the questionnaires and distributed to 200 respondents in five locations of â€œpasar indukâ€ in Jakarta by applying quota sampling technique. The collected data were analyzed using factor analysis technique by involving practitioners and academics in the process of identifying and naming the variables. The result proves that the factors that affect the customers reluctant to become BPR customers caused by five factors, namely: attitude (consumer rating for not to choose BPR); subjective norms (the pressure of the relatives); perceived behavioral control (customers control to decide not to choose BPR); intention (the intention not to choose BPR; and behavior (action not to choose BPR).